Letter (copy) : Spain - deputation to Prime Minister - Tewson, Vincent
012b-0070-001 Secretary's. HVT/FC/EK/598. 19th January, 1939. Mr. R. Willis, London Trades Council, 24, Thavies Inn, Holborn, London, E.C.1. Dear Mr. Willis, Spain - Deputation to Prime Minister. I thank you for your letter of the 18th instant, together with enclosures, regarding the situation in Spain. This question is at present under very urgent consideration and whilst immediate steps are being taken in regard to the matter, the subject is to be further discussed at the National Council of Labour meeting on Tuesday next. Yours sincerely, Assistant Secretary. 292/946/12b/70